Implementation of Regional Regulation No. 5 of 2015 on The Protection of Sustainable Food Agricultural Land in Sorong Regency - Subur Subur; Muhammad Guzali Tafalas; Adianto Adianto (Lembaga Publikasi Ilmiah Nusantara, 2025)
Agricultural land is one of the most strategic resources in supporting food security at both the national and regional levels. However, the rapid expansion of urbanization and economic development often leads to the conversion of productive agricultural land for non-agricultural purposes. This study examines the implementation of Regional Regulation No. 5 of 2015 concerning the Protection of Sustainable Food Agricultural Land (PLP2B) in Sorong Regency, Southwest Papua Province, Indonesia. The research employs Van Meter and Van Horn’s policy implementation model, which emphasizes six variables: policy standards and objectives, policy resources, inter-organizational communication and enforcement, characteristics of implementing agencies, attitudes of implementers, and socio-economic and political conditions. A qualitative descriptive approach was used, supported by survey data. A total of 111 farmers, 5 village officials, and 8 representatives from key government agencies (Department of Agriculture, Bappeda, Environmental Agency, and DPMPTSP) participated in the study through proportional random and purposive sampling techniques. Data were collected using questionnaires, in-depth interviews, and direct observations. The results indicate that although most farmers (76%) support maintaining agricultural land despite economic pressures, the implementation of PLP2B remains suboptimal. Limited financial resources, weak coordination among agencies, lack of public awareness, and socio-economic pressures such as high land prices and urbanization are the primary obstacles. The study concludes that stronger institutional capacity, effective communication, consistent spatial planning integration, and farmer-oriented economic incentives are urgently required to safeguard agricultural land and ensure regional food security.